Effect of the morphology of hard segment domains in bio-based polyurethanes on the filtration properties of nanostructured filters - Simona Uhercova; Dusan Kimmer; Muhammad Yasir; Lenka Lovecka; Miroslava Kovarova; Tomas Plachy; Vladimir Sedlarik (Polymer Testing)
Renewable polymers have attracted significant attention in recent years as alternatives to fossil-based materials, driven by concerns about the depletion of such resources and the need for sustainable development. This study reports on the synthesis of polyurethanes from renewable biomass-derived diols, and their subsequent application in nanostructured air filters produced via electrospinning. Comparison is made of the properties of bio-based polyurethane samples that varied in the molecular weights of the inherent poly (1,3-propanediol) soft segments. Their physical-mechanical properties were analysed, along with the morphology and filtration performance of the nanostructures. It was found that the arrangement of the hard segments affected both phase temperature transitions (i.e. the glass transition and melting point) of the prepared polyurethanes. Positive effect hard segments domain arrangements and the best filtration properties were observed for a bio-polyether-based aromatic polyurethane prepared with molar ratio of diisocyanate:polyether polyol:chain extender of 4.7:1:3.7 and a molar mass of used renewable polyol 1000 g/mol, a nanostructure boasting the largest pore size of those tested. Filter with pressure drop of 49 Pa only possessed quality factor exceeding 0.045 Pa-1. The work confirms the fact that the effects of fiber diameter and pore size on the filtration properties of nanostructured air filters fabricated to eliminate ultra-fine particles cannot be judged separately.